A regra de S. Bento, norma de vida monástica : sua problemática moderna e edições em português. "Rectissima norma vitae", RB. 73, 13 - Dias, Geraldo José Amadeu Coelho, 1934- (2002)
Saint Benedict's Regula (RB) was written during the High Middle Ages (5m century) and, since then, has been the primary and accepted basis of the rule of Catholic monastic orders. However, in the late quarter of the 20m century, and thanks to the studies of a French Benedictine monk, D. Adalberto De Vogiie, the originality of the Benedictine Regula was questioned as it was compared to the anonymous "Regula Magistri', a document that, although already known in his time, had never been considered very significant. Despite De Vogue's theory is today generally accepted, there are still some resistance. Confirming the merit of the French author's studies on the old monastic life, as well as his studies on the Benedict's Regula, we seek to demonstrate the primacy of the RB, in spite of the problems this text raises, review arguments and examine the two Portuguese editions.